Quiosco Interactivo para la Universidad San Buenaventura Cali (2017)
The definition of interactive kiosks, arises from the need to have elements that support the communications and information system that exists within the university. Providing students an interactive and easily accessible on-campus tool with basic information to consult.It is demonstrated how the use of interactive kiosks, has successfully impacted other projects, where it is required to provide information of easy and agile access to users.It also describes the process of researching and choosing the software and hardware tools used for the development of the project, making comparisons between the various free web development frameworks, that currently exist and the hardware used to develop the project. Research and comparison of the different microcomputers and input devices are carried out, which can be used for the development of the project, choosing based on technical and knowledge criteria. The study, design and construction of an interface that gives users a complete experience as to what their needs are required. The choice of interfaces is made through iterations of tests with users, which not only validate the user interface but also the experience they get when interacting with the software.